A comparison of the burden of cancers between 1990 and 2019 in Iran: A national and subnational study - Mitra Darbandi; Zahra Khorrami; Ali Karamoozian; Omid Aboubakri; Mahsa Miryan; Leila Rezakhani; Fatemeh Khosravi Shadmani (PLoS ONE, 2025)
Background Cancer is a rapidly increasing global problem, and one of the leading causes of burden and mortality. This study aims to compare the burden of cancer in Iran between the year 1990 and 2019. Methods We used Global Burden of Disease data on cancer from 1990 to 2019 by province, year, age group, and sex. We then estimated the trend of age standardized mortality and Disability-Adjusted Life Years (DALYs) of the cancers by sex. Age pattern and geographical variation in the ranking of cancers were assessed at national and sub-national levels from 1990 to 2019. Results The mortality rate decreased from 102 (95% UI: 91, 111) to 96 (95% UI: 88, 103) per 100000 population. Additionally, the DALYs rates decreased from 2619 (95% UI: 2357, 2852) to 2321 (95% UI: 2116, 2497) per 100000 between 1990 and 2019. Both of the mortality and DALYs rate from cancers increased with age. These indicators were significantly higher in men than in women across all age groups. Consequently, the mortality rate and DALYs per 100,000 of cancers were higher in the northwest and northeast of Iran. Notably, stomach cancer was identified as the leading cause of cancer mortality in 23 provinces of Iran in 2019. The highest percentage change of DALYs per 100,000 rate between 1990 and 2019 was observed for malignant skin melanoma, stomach cancer, and cervical cancers with rate of −41.1, −40.1, and −38.4, respectively. Conclusion Overall, the mortality and DALYs per 100,000 rates of all cancers for both sexes in Iran have decreased between 1990 and 2019. However, there is an increasing trend in types of cancers, such as pancreatic, ovarian, and breast cancers.